Comparison of Intratracheal and Intravenous Inoculation of Sheep Erythrocytes in the Induction of Local and Systemic Immune Responses - Stein-Streilein, Joan (1979)
The interdependence of the local and systemic immune systems in the development of the immune responses relating to the lung was evaluated. Hamsters were inoculated with 10(9) sheep erythrocytes (SRBC) via local (intratracheal) or systemic (intravenous) routes of immunization. The local immune response was quantitated by the specific antibody-forming cell (sAFC) response in the pulmonary draining lymph nodes (pdLNC). sAFC in the spleens and serum hemagglutination titers evaluated the systemic immune response. The local inoculation of antigen was superior for induction of the maximal numbers of immunoglobulin M (IgM) and non-IgM sAFC in the pdLNC at 4 days post-immunization. However, the local response coould be enhanced by a concomitant splenic response. The local route of inoculation did not consistently induce an sAFC response in the spleen, but when the spleen was involved, two unique observations were recorded regarding the IgM response: (i) an approximate twofold increase in the numbers of sAFC was seen in the pdLNC on day 7 post-inoculation in animals that had a splenic sAFC response; and (ii) the appearance of an early (day 4) serum IgM hemagglutination titer was observed in the animals with a splenic sAFC response. However, the appearance of IgG serum hemagglutination titers was independent of the indirect sAFC response in the spleen but correlated with the appearance of indirect sAFC response in the pdLNC. As expected, intravenous inoculation of antigen was superior for inducing a systemic IgM response. We concluded that the local and systemic immune responses are related and interdependent in providing immune reactivity related to the lung. Whereas the systemic response enhanced both the serum IgM titer and the specific IgM antibody-forming cell response in the draining nodes, we observed that the local response was sufficient for the IgG serum hemagglutination titer even in the absence of a splenic sAFC response.